1996
DOI: 10.1200/jco.1996.14.5.1604
|View full text |Cite
|
Sign up to set email alerts
|

p53 and bcl-2 expression correlates with clinical outcome in a series of node-positive breast cancer patients.

Abstract: p53 expression appears to be indicative of clinical outcome in postmenopausal patients treated with tamoxifen. Whether p53 overexpression and weak bcl-2 expression are indicators of biologic aggressiveness, regardless of treatment, or of hormone resistance remains to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
84
4
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 14 publications
10
84
4
3
Order By: Relevance
“…These findings were in parallel with those results in colorectal cancer, breast cancer, non-small-cell lung cancer, renal cancer and head and neck cancer. (Ofner et al, 1995;Silvestrini et al, 1996;Fontanini et al, 1995;Hirata et al, 2009;Lehnerdt et al, 2009). Accordingly in those studies Increased Bcl-2 expression is associated to favorable outcome.…”
Section: Discussionmentioning
confidence: 97%
“…These findings were in parallel with those results in colorectal cancer, breast cancer, non-small-cell lung cancer, renal cancer and head and neck cancer. (Ofner et al, 1995;Silvestrini et al, 1996;Fontanini et al, 1995;Hirata et al, 2009;Lehnerdt et al, 2009). Accordingly in those studies Increased Bcl-2 expression is associated to favorable outcome.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, they all lack PR expression (Lykkesfeldt et al, 1994(Lykkesfeldt et al, , 1995. Several clinical studies have shown that the Bcl-2 expression in breast tumours is strongly correlated to both ERα and PR expression, and Bcl-2 expression is an indicator of a favourable outcome following endocrine treatment (Gee et al, 1994;Lipponen et al, 1995;Silvestrini et al, 1996;Elledge et al, 1997;Keen et al, 1997;Kobayashi et al, 1997;Olopade et al, 1997;Holmqvist et al, 1999). The decreased Bcl-2 expression associated with decreased ERα expression, and lack of response to antioestrogens observed in the resistant cell lines is in concert with the above-mentioned clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The survival of patients presenting tumours which express Bcl-2 protein may be better, unchanged, or worse than of those with similarly classi®ed tumours which lack Bcl-2 (Campos et al, 1993;Herod et al, 1996;Lepelley et al, 1995;Pezzella et al, 1992;Piris et al, 1994) and high Bcl-2 expression has been reported to be associated with low tumour cell proliferation (Silvestrini et al, 1996;Wilson et al, 1997). Whilst a number of explanations may be o ered to account for such observations, our results suggest that di erential e ects of Bcl-2 on cell cycle arrest, the activity of wt p53 and the availability of additional, micro-environmental signals that promote cell survival or cell growth may critically determine ultimate tumour cell fate.…”
Section: Discussionmentioning
confidence: 99%